Graphene‐Supported Pyrene‐Modified Cobalt Corrole with Axial Triphenylphosphine for Enhanced Hydrogen Evolution in pH 0–14 Aqueous Solutions. Issue 22 (21st September 2017) - Li, Xialiang; Lei, Haitao; Guo, Xiaojun; Zhao, Xueli; Ding, Shuping; Gao, Xueqing; Zhang, Wei; Cao, Rui
Abstract: A cobalt complex of 5, 15‐bis(pentafluorophenyl)‐10‐(4)‐(1‐pyrenyl)phenyl corrole that contains a triphenylphosphine axial ligand (1 ‐PPh3 ) was synthesized and examined as an electrocatalyst for the hydrogen evolution reaction (HER). If supported on graphene (G), the resulting1 ‐PPh3 /G material can catalyze the HER in aqueous solutions over a wide pH range of 0–14 with a high efficiency and durability. The significantly enhanced activity of1 ‐PPh3 /G, compared with that of its analogues1 ‐py/G (the Co‐bound axial ligand is pyridine instead of triphenylphosphine) and2 ‐py/G (Co complex of 5, 10, 15‐tris(pentafluorophenyl)corrole), highlights the effects of the pyrenyl substituent and the triphenylphosphine axial ligand on the HER activity. On one hand, the pyrenyl moiety can increase the π–π interactions between1 and graphene and thus lead to a fast electron transfer from the electrode to1 . On the other hand, the triphenylphosphine axial ligand can increase the electron density (basicity) of Co and thus make the metal center more reactive to protons at the trans position through a so‐called "push effect". This study concerns a significant example that shows the trans effect of the axial ligand on the HER, which has been investigated rarely. The combination of various ligand‐design strategies in one molecule has been realized in1 ‐PPh3 to achieve a high catalytic HER performance. These factors are valuable to be used in other molecular catalyst systems. Abstract : In the company of corroles : Graphene‐supported cobalt corroles are active and stable catalysts for the hydrogen evolution reaction in water over a wide pH range of 0–14. The introduction of a pyrenyl group to the corrole macrocycle and the use of a triphenylphosphine axial ligand on Co improve the catalytic efficiency significantly.